Involving family and friends helps sustainable diets last longer - Rosaly Severijns; Igor Asanov; Sandra Streukens; Stephan B. Bruns; Pablo Moleman; Jasperina Brouwer; Joey van Griethuijsen; Sebastien Lizin (npj Climate Action, 2024)
Abstract Reducing animal product consumption is a necessary action to mitigate climate change and other environmental issues. We tested and compared the effectiveness of an individual and a social app-based 30-day challenge in reducing animal product consumption. Through a pre-registered field randomized controlled trial (n = 1213), we find both conditions reduced animal product consumption by 16–17% compared to the control group, with a lasting effect only for the social treatment (encouragement to involve family and friends) 3 months after the intervention. The effects were largest for meat consumption and those who consumed meat at the baseline. Additionally, associated greenhouse gas emissions decreased by 21–24% and are still significantly reduced 3 months after both interventions, with a larger effect for the social treatment. Our findings suggest that app-based animal product-free challenges are a cost-effective way (~€13–25 per tCO2-eq assuming a 1-year lasting effect) to translate intentions into lasting dietary change, especially when involving the social environment and targeting meat eaters.